Studying of Metal elements, Urea and Creatinine in Cerebrospinal Fluid for Children with Hydrocephalus Patients - Lelas Farhan Bdaiwi; Sayran Sattar Saleh; Luay Abed Al-Helaly (Kirkuk Journal of Science, 2018)
The research includes studying the effect of hydrocephalus on metal elements and kidney function in the cerebrospinal fluid (CSF) which include of parameters : Iron (Fe), Cupper (Cu), Zinc(Zn), Magnesium (Mg), Sodium (Na), Potassium (K), Calcium (Ca), Phosphorus (P), Chloride (Cl), Urea and Creatinine. The study was done on (176) sample had hydrocephalus (110) were male and (66) were female and (67) were healthy children as control group( 39) were male and (33) were female the age of children with hydrocephalus and control group ranged from 1-14 month for both sex. The results showed there was a significant increase in Fe, Cu, K, Na, Cl and P in the CSF for children with hydrocephalus patients in comparison with healthy group for both sex, and a significant decrease was shown in the levels of Zn, Mg and Ca. Beside of that, the results showed the kidney functions were affected by significant high levels of urea and creatinine in CSF for both sexes of hydrocephalus patients in comparison with healthy group.